FENOMENA PERILAKU TOXIC RELATIONSHIP DALAM HUBUNGAN BERPACARAN KAWULA MUDA DI JAKARTA SELATAN - Ambarita, Priscilia; Punia, I Nengah; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 2 (2023): JISSOROT, 2023)
This study aims to analyze toxic relationship behavior among young adults in dating relationships in South Jakarta using a qualitative approach. Data will provide a detailed overview of young adult,' experiences with toxic relationships, employing Robert J. Sternberg's triangular theory of love. Results reveal diverse forms of toxic relationships, including verbal, emotional, and physical violence, such as infidelity, open relationships, and possessive behavior. Impact encompasses diminished self-confidence, mental and physical health issues, and financial losses. Anticipation and prevention of toxic relationship behavior are vital. Healthy communication and partner selection are crucial to evade toxic relationships.